Empowering women in the workplace: Assessing female employees' readiness for flexible work arrangements - Yuen, Yee Yen; Teoh, Wendy Ming Yen; Teoh, Ming-Li; Thye, Wan Ying (ESS Publications, 2024)
The paper examines assessing female employees’ readiness for flexible work arrangements and empowering women in the workplace. The adoption of flexible work arrangements (FWA) practices in Asian countries is prominent. Despite the recognized benefits that FWAs can provide in terms of employee’s well-being and business sustainability, their implementation is still relatively limited. Hence, the purpose of this study is to identify the factors (family responsibilities, FWA benefits, career advancement, company policy, and supportive workplace) that influence Malaysian female employees’ readiness for FWAs. In this study, the Person-Environment (PE) Fit Theory is employed as a framework to comprehend an individual’s readiness for adopting FWAs. To gather data, 200 surveys were distributed online to female employee respondents using the convenience sampling method. The data analysis was carried out. The findings demonstrate an association between female employees' readiness for FWAs and FWA benefits, career advancement, and company policy. However, family responsibilities and supportive workplaces indicate insignificantly on female employees’ readiness in relation to FWAs, warranting further investigation. This study provides valuable insights to various stakeholders, like organizations, practitioners, policymakers, and the government, in understanding and addressing the readiness of female employees for FWAs and serves as a research foundation for more informed decision-making across organizations in Malaysia. Female employees often face challenges in balancing work and family responsibilities, and if a company could provide flexible arrangements, it could create a supportive environment that can help retain skilled female professionals.